Towards a scalability approach for risk mitigation in electrical systems. Issue 1 (2018) - Larbi, El Yasmine Ait Si; Belalem, Ghalem; Beldjilali, Bouziane
Electrical energy has been used for decades to power domestic equipment, small and large industries and transportation with the electrification of everything, the availability of electricity becomes crucial. In order to guarantee the continuity of the electrical energy supply, companies must have effective means to prevent risks that may arise on the electricity networks. This paper is focused on the risk of insufficient power supply for end customers. The solutions consist of upsizing the existing equipment configuration and/or add other equipments in order to guarantee an increase in power supply. The proposed approach is based on distributed artificial entities corresponding to the distributed enterprise actors. We propose a control system, based on a decision making system to help decision-makers to take the best scalability solution. The results show that the degree of effectiveness of each type of scalability depends on one electrical system configuration to another.